Rethinking soil contamination assessment for urban brownfield management: from total hazard to bioavailability - Rachel Seillier; Frédéric Paran; Benjamin Pauget; Cédric Challaye; Steve Peuble; Frédéric Gallice; Jérémie Riquier; Baptiste Bouillot; Olivier Faure (Chemosphere, 2025)

Whey draining of goat milk cheese: A model study using frontal filtration - Manon Basset; Julien Monteil; Valentin Demaille; Benjamin Faure; Fernando Leal-Calderon; Christelle Harscoat-Schiavo; Raphaëlle Savoire (Journal of Food Engineering, 2023)

Nile blue as reporter dye in salt aggregation based-colorimetric aptasensors for peptide, small molecule and metal ion detection - Benoît Chovelon; Eric Peyrin; Mailys Ragot; Nassim Salem; Truong Giang Nguyen; Benjamin Auvray; Mickael Henry; Mel-Alexandre Petrillo; Emmanuelle Fiore; Quentin Bessy; Patrice Faure; Corinne Ravelet (Analytica Chimica Acta, 2023)

Investigation of the geographical scale of adaptive phenological variation and its underlying genetics in A rabidopsis thaliana - Benjamin Brachi; Romain Villoutreix; Nathalie Faure; Nina Hautekèete; Yves Piquot; Maxime Pauwels; Dominique Roby; Joël Cuguen; Joy Bergelson; Fabrice Roux (Molecular Ecology, 2013)
Despite the increasing number of genomic tools, identifying the genetics underlying adaptive complex traits remains challenging in the model species A rabidopsis thaliana . This is due, at least in part, to the lack of data on the geographical scale of adaptive phenotypic variation. The aims of this study were (i) to tease apart the historical roles of adaptive and nonselective processes in shaping phenological variation in A . thaliana in F rance and (ii) to gain insights into the spatial scale of adaptive variation by identifying the putative selective agents responsible for this selection. Forty‐nine natural stands from four climatically contrasted French regions were characterized (i) phenologically for six traits, (ii) genetically using 135 SNP markers and (iii) ecologically for 42 variables. Up to 63% of phenological variation could be explained by neutral genetic diversity. The remaining phenological variation displayed stronger associations with ecological variation within regions than among regions, suggesting the importance of local selective agents in shaping adaptive phenological variation. Although climatic conditions have often been suggested as the main selective agents acting on phenology in A . thaliana , both edaphic conditions and interspecific competition appear to be strong selective agents in some regions. In a first attempt to identify the genetics of phenological variation at different geographical scales, we phenotyped worldwide accessions and local polymorphic populations from the F rench RegMap in a genome‐wide association ( GWA ) mapping study. The genomic regions associated with phenological variation depended upon the geographical scale considered, stressing the need to account for the scale of adaptive phenotypic variation when choosing accession panels for GWAS .